The night ends with fire [large type] - Song, K. X. ([Night Ends With Fire], 2025)
"The Three Kingdoms are at war, but Meilin's father refuses to answer the imperial draft. Trapped by his opium addiction, he plans to sell Meilin for her dowry. But when Meilin discovers her husband-to-be is another violent, ill-tempered man, she realizes that nothing will change for her unless she takes matters into her own hands. The very next day, she disguises herself as a boy and enlists in her father's place. In the army, Meilin's relentless hard work brings her recognition, friendship and a growing closeness with Sky, a prince turned training partner. But has she simply exchanged one prison for another? As her kingdom barrels toward destruction, Meilin begins to have visions of a sea dragon spirit that offers her true power and freedom, but with a deadly price. With the future of the Three Kingdoms hanging in the balance, Meilin will need to decide whom to trust--Sky, who inspires her loyalty and love; the sea dragon spirit, who has his own murky agenda; or an infuriating enemy prince who makes her question everything she once knew about her kingdom and about her own heart."--